HUBUNGAN POSISI DUDUK DAN LAMA DUDUK DENGAN KELUHAN LOW BACK PAIN PADA PEKERJA ADMINISTRASI PT. XVL BATAM - Juhanda Kartika Wijaya (Journal of Innovation Research and Knowledge, 2026)
Low back pain (LBP) is a common musculoskeletal complaint among office workers, often associated with poor sitting posture and prolonged sitting duration. Administrative staff, who spend most of their working hours seated, are particularly vulnerable to this condition. This study aimed to analyze the relationship between sitting position and sitting duration with LBP complaints among administrative workers at PT. XVL, Batam City, in 2024. This quantitative study used a cross-sectional design involving a total sampling of 30 administrative workers. Data were collected using structured questionnaires and analyzed using univariate and bivariate (Chi-Square/Fisher’s Exact) statistical tests. The results showed that 60.0% of workers had a non-ergonomic sitting position, 53.3% sat for long durations, and 73.3% experienced LBP complaints. Bivariate analysis revealed a significant association between sitting position and LBP complaints (p = 0.041; OR = 0.400; 95% CI 0.066–2.437), as well as between sitting duration and LBP complaints (p = 0.026; OR = 0.278; 95% CI 0.046–1.692). These findings indicate that non-ergonomic sitting posture and prolonged sitting duration significantly increase the risk of LBP among administrative workers. Companies are recommended to provide ergonomics training, ergonomic furniture, and scheduled stretching breaks to reduce this occupational health risk.